THE EFFECT OF TRANSFORMATIONAL LEADERSHIP BEHAVIOR ON ORGANIZATIONAL PERFORMANCE IN GOLD INDUSTRY OF SAUDI ARABIA - Alhshedi, Aref; Bardai, Barjoyai; Al-Dubai, Maged (Journal of process management and new technologies, 2020)
This paper mainly aims at investigating the effect of transformational leadership behaviour on organizational performance, as well as other factors such as psychological ownership, working environment, employee involvement, incentives, and employee motivation take into account their effect on organizational performance. To achieve the objectives of the study, quantitative research approach was applied through a questionnaire specifically designed to collect primary information from the samples of the study, which consisted of (250) managers in gold shops in Jaddah. The collected data was analysed using SPSS 20.0. The results showed that transformational leadership behaviour, psychological ownership, working environment, employee involvement, incentives, and employee motivation significantly affect organizational performance in the Saudi Arabian gold industry. Finally, the researcher recommended ways to promote the concept of transformational leadership behaviour in the gold sector in Saudi Arabia at various administrative levels by holding courses and seminars.Transformational Leadership, Organizational Performance, Gold Industry.